ANALISIS PENILAIAN SAHAM PT ADHI KARYA (Persero), Tbk. PASCA KEBIJAKAN INSENTIF PAJAK - , Heribertus Andi Noviastoko, S.E. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
ThisÂ researchÂ aimsÂ toÂ estimateÂ theÂ intrinsicÂ valueÂ ofÂ equityÂ ofÂ PTÂ AdhiÂ KaryaÂ (Persero)Â Tbk.Â postÂ aÂ 5Â percentÂ taxÂ incentiveÂ policyÂ byÂ usingÂ  theÂ methodÂ ofÂ discountedÂ cashÂ flowÂ andÂ relativeÂ valuationÂ methods.Â  ThisÂ  studyÂ becomesÂ  interestingÂ  toÂ  doÂ  becauseÂ  ofÂ  PTÂ  AdhiÂ  KaryaÂ  (Persero)Â  Tbk.Â  hadÂ releasedÂ Â itsÂ stakeÂ byÂ 49Â percent,Â thusÂ entitledÂ toÂ aÂ taxÂ incentiveÂ ofÂ 5Â percentÂ andÂ theÂ policyÂ isÂ validÂ fromÂ JanuaryÂ 2011.Â TheÂ dataÂ usedÂ consistÂ ofÂ financialÂ statementsÂ  dataÂ  PTÂ  AdhiÂ  KaryaÂ  (Persero)Â  Tbk.,Â  theÂ  informationÂ  inÂ  annualÂ reports,Â financialÂ statementsÂ ofÂ theÂ comparisonÂ companies,Â dataÂ comparisonÂ companyÂ stockÂ price,Â riskÂ freeÂ interestÂ rate,Â asÂ wellÂ asÂ otherÂ supportingÂ data.Â AnalysisÂ usingÂ discountedÂ cashÂ flowÂ methodÂ isÂ doneÂ byÂ stages:Â anÂ analysisÂ ofÂ salesÂ  orÂ  revenueÂ  projections,Â  projectionsÂ  ofÂ  financialÂ  statements,Â  projectedÂ freeÂ cashÂ flowÂ (freeÂ cashÂ flow),Â determiningÂ theÂ discountÂ rateÂ (WACC),Â  theÂ determinationÂ ofÂ theÂ finalÂ valueÂ (terminalÂ value),Â andÂ valueÂ estimates.Â Â AnalysisÂ  byÂ  usingÂ  relativeÂ  valuationÂ  methodÂ  beginsÂ  byÂ  determiningÂ comparisonÂ  companiesÂ  inÂ  theÂ  sameÂ  fieldÂ  ofÂ  businessÂ  subsequentÂ  toÂ  chooseÂ andÂ setÂ theÂ multiplierÂ digitsÂ (multiples)Â thatÂ willÂ beÂ usedÂ toÂ convertÂ theÂ bookÂ valueÂ  ofÂ  theÂ  relevantÂ  variablesÂ  fromÂ  theÂ  PTÂ  AdhiÂ  KaryaÂ  (Persero)Â  Tbk.Â  toÂ estimateÂ theÂ marketÂ valueÂ ofÂ equity.Â MultiplesÂ usedÂ are:Â PERÂ (PriceÂ EarningÂ Ratio)Â  andÂ  PBVÂ  (PriceÂ  toÂ  BookÂ  Value).Â  FromÂ  theÂ  researchÂ  resultsÂ canÂ beÂ obtainedÂ byÂ reconcilingÂ theÂ intrinsicÂ valueÂ ofÂ PTÂ AdhiÂ KaryaÂ (Persero)Â TbkÂ inÂ theÂ rangeÂ ofÂ Rp1.241,Â 871Â perÂ share.Â ThusÂ theÂ stockÂ priceÂ asÂ ofÂ theÂ valuationÂ workÂ PTÂ AdhiÂ KaryaÂ (Persero)Â Tbk.Â showÂ undervalued.Â ThisÂ indicatesÂ thatÂ theÂ stockÂ  marketÂ  hasÂ  notÂ  appreciatedÂ